The Macroeconomics Factors and the Crisis-induced Sentiment of Fears Impact on Indonesian Government Bond Yield - Bhakta Narayana, I Gusti Ngurah Agung Arya; Lubis, Arief Wibisono (Jurnal Ekonomi Kuantitatif Terapan, 2023)
Great Financial Crisis 2008 and the COVID-19 crisis are two world crises that happened in the last 20 years, yet there’s so little literature that connects the sentiment of fear to the bond market. This study focuses on analyzing the impact of the sentiment of fear caused by the two crises that occurred in Indonesia, namely the Great Financial Crisis in 2008 and the COVID-19 Pandemic, along with macroeconomic factors to 10-year Indonesian government bond yields using VECM methods. The results showed that only the Federal Reserve interest rate has a significant impact on the government bond yield in both crises, while the rest is not significant. This result shows that in both crises, the Indonesian government bond yield was affected by only the Federal Reserve’s reaction to the crises, while not considering how both crises could cause negative sentiment from the investors.